Opposite Influence of Light and Blindness on Pituitary–Gonadal Function - Bellastella, Antonio; De Bellis, Annamaria; Bellastella, Giuseppe; Esposito, Katherine (Frontiers in Endocrinology, 2014)
Some environmental factors may influence the pituitary-gonadal function. Among these, light plays an important role in animal and in humans. The effect of light on the endocrine system is mediated by the pineal gland, through the modulation of melatonin secretion. In fact, melatonin secretion is stimulated by darkness and suppressed by light, thus its circadian rhythm peaks at night. Light plays a favourable action on the hypothalamic-pituitary axis likely inhibiting melatonin secretion, even if the exogenous melatonin administration does not seem to impair the hormonal secretions of this axis. The basal and rhythmic pituitary-gonadal hormone secretions is regulated by a central clock gene and some independent clock genes present in the peripheral tissues. Light is able to induce the expression of some of these genes, thus playing an important role in regulating the hormonal secretions of pituitary -gonadal axis and the sexual and reproductive function in animals and humans. The lack of light stimulus in blind subjects induces increased plasma melatonin concentrations with a free-running rhythm of secretion, which impairs the hormonal secretions of pituitary-gonadal axis, causing disorders of reproductive processes in both sexes.